2014
DOI: 10.3892/or.2014.2997
|View full text |Cite
|
Sign up to set email alerts
|

ZNF703 acts as an oncogene that promotes progression in gastric cancer

Abstract: ZNF703, a member of the NET/Nlz family of zinc finger transcription factors, contributes to aspects of developmental growth and patterning across evolutionarily diverse species. ZNF703 has been identified as a novel oncogene in human breast cancer. In the present study, we investigated the expression of ZNF703 in gastric carcinoma and attempted to determine, using cell line models, its biological actions. Using immunohistochemistry, we analyzed the ZNF703 protein expression in 120 clinicopathologically charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…ZNF703 is a zinc finger transcription factor belongs to NET/NLZ family and contributes to the development and progression of various cancer, including NSCLC, breast cancer, gastric cancer (GC), and colorectal cancer (CRC). [40][41][42] Moreover, ZNF703 is involved in the activation of the Akt/mammalian target of rapamycin (mTOR) signaling pathway in breast cancer cell lines. 43 Therefore, Shi et al 11 detected the potential roles of ZNF703 in breast cancer cell lines and discovered that ZNF703 is augmented in breast cancer tissues and cell lines.…”
Section: Breast Cancermentioning
confidence: 99%
“…ZNF703 is a zinc finger transcription factor belongs to NET/NLZ family and contributes to the development and progression of various cancer, including NSCLC, breast cancer, gastric cancer (GC), and colorectal cancer (CRC). [40][41][42] Moreover, ZNF703 is involved in the activation of the Akt/mammalian target of rapamycin (mTOR) signaling pathway in breast cancer cell lines. 43 Therefore, Shi et al 11 detected the potential roles of ZNF703 in breast cancer cell lines and discovered that ZNF703 is augmented in breast cancer tissues and cell lines.…”
Section: Breast Cancermentioning
confidence: 99%
“…There exist a number of publications describing the correlation between the expression of ZNF280B and the growth of various types of cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). For example, Gunn et al (22) reported that ZNF280B acts as a tumor suppressor in chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies has reported that ZNF proteins serve critical roles in human cancers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). For example, ZNF703 acts as an oncogene in invasive gastric carcinoma, and its expression levels are correlated with gastric carcinoma progression (16). The downregulation of ZNF306 expression reduces tumorigenicity in colorectal cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…ZNF703, a member of zinc finger transcription factors, is located on chromosomes 8 (8p11.23), contributes to aspects of growth and patterning across evolutionarily diverse species [22] . ZNF703 has been identified as a novel oncogene in human breast cancer [23] , colorectal cancer [24] , gastric cancer [22] , etc.…”
Section: Regulate Znf703 Genementioning
confidence: 99%
“…ZNF703 has been identified as a novel oncogene in human breast cancer [23] , colorectal cancer [24] , gastric cancer [22] , etc. ZNF703 has been demonstrated promotes ER(−) breast carcinoma cell proliferation and suppresses apoptosis in vivo, and recently studies showed that ZNF703 could be regulated by SPRY4-IT1 as a downstream target gene of SPRY4-IT1 [14] .…”
Section: Regulate Znf703 Genementioning
confidence: 99%